2008
DOI: 10.1007/s11740-008-0077-5
|View full text |Cite
|
Sign up to set email alerts
|

New developments on the use of polymeric materials in sheet metal forming

Abstract: Advanced polymers offer at the present time concrete possibilities in reducing the product development time and production of prototypes and small series of sheet metal parts. However, the applicability of such materials requires different approaches in comparison to conventional materials for sheet metal forming dies. This paper presents investigation results dealing with tribological and tool design aspects for the use of polymeric materials in sheet metal forming. Friction and wear of sheets with different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Good friction behavior of polymers makes them attractive as tooling materials [7]. Tribological properties of polymer composite tools for contact with metals were studied by Park and Colton [8] as well as Liewald and de Souza [9]. Park and Colton also investigated the failure modes of polymer composite deep drawing dies, including fracture, wear and plastic deformation [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Good friction behavior of polymers makes them attractive as tooling materials [7]. Tribological properties of polymer composite tools for contact with metals were studied by Park and Colton [8] as well as Liewald and de Souza [9]. Park and Colton also investigated the failure modes of polymer composite deep drawing dies, including fracture, wear and plastic deformation [10].…”
Section: Introductionmentioning
confidence: 99%
“…may cause this anisotropy [16]. However, most numerical investigations into the use of polymer AM tooling for sheet metal forming have used simple isotropic material models for the polymer tooling [9,10,17]. The authors previously demonstrated the importance of using anisotropic material models for accurately predicting the elastic-plastic deformation of FDM CF-Nylon dies during stamping of HSS sheets using nite element analysis [18].…”
Section: Introductionmentioning
confidence: 99%
“…One way to ensure appropriate friction conditions is the selection of the tool material (Schmoeckel et al, 1986). Because of the requirements regarding wear resistance and form stability, deep drawing tools are mainly made of tooling steel or cast iron (Liewald & de Souza, 2008). In addition to commonly used metal tools, it is possible to use tools made of elastomers or composites based on metals and plastics (Bergweiler et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to commonly used metal tools, it is possible to use tools made of elastomers or composites based on metals and plastics (Bergweiler et al, 2021). Liewald and de Souza (2008) investigated tribological and tool design aspects for the use of polymeric materials (polyurethane with Al hydroxide and Al powder fillers) in sheet metal forming. They developed a new test method for measuring polymer/sheet wear.…”
Section: Introductionmentioning
confidence: 99%
“…Liewald et al tested polymeric die materials in sheet metal forming and found that by using polymeric materials with high mechanical properties it was possible to produce parts with a dimensional accuracy sufficient for most applications, even using high-strength steels. [13]. Kuo et al fabricated sheet metal forming dies in epoxy resin filled with zirconia (ZrO 2 ) to deform Al-Mg alloy blanks; their results demonstrated a forming capacity at a thickness of 0.35 mm [14].…”
Section: Introductionmentioning
confidence: 99%